Production of cold-adapted enzymes by filamentous fungi from King George Island, Antarctica - Duarte, Alysson Wagner Fernandes; Barato, Mariana Blanco; Nobre, Fernando Suzigan; Polezel, Danilo Augusto [UNESP]; de Oliveira, Tássio Brito [UNESP]; dos Santos, Juliana Aparecida [UNESP]; Rodrigues, André [UNESP]; Sette, Lara Durães [UNESP] (Springer Nature, 2018)
Antarctic environments are characterized by polar climate, making it difficult for the development of any form of life. The biogeochemical cycles and food web in such restrictive environments may be exclusively formed by microorganisms. Polar mycological studies are recent and there is much to know about the diversity and genetic resources of these microorganisms. In this sense, the molecular taxonomic approach was applied to identify 129 fungal isolates from marine and terrestrial samples collected from the King George Island (South Shetland Islands, Maritime Antarctic). Additionally, the production of cold-adapted enzymes by these microorganisms was evaluated. Among the 129 isolates, 69.0% were identified by ITS-sequencing and affiliated into 12 genera. Cadophora, Geomyces, Penicillium, Cosmospora, and Cladosporium were the most abundant genera. Representatives of Cosmospora were isolated only from terrestrial samples, while representatives of the others genera were recovered from marine and terrestrial samples. A total of 29, 19, and 74 isolates were able to produce ligninolytic enzymes, xylanase, and l-asparaginase, respectively. Representatives of Cadophora showed great ability to produce lignin peroxidase (LiP) and laccase at 15.0 °C in liquid medium, while representatives of Penicillium and non-identified fungi were the best producers of xylanase and l-asparaginase at 20.0 °C. The high number of fungi able to produce enzymes at moderate temperature reveals their potential for industrial production and biotechnological applications. The present study broadens the knowledge of fungal diversity associated with the southern polar region. Additionally, data from molecular taxonomy suggest that two filamentous fungi may be considered as potential new species.
Keywords: Extremophiles; l-Asparaginase; Ligninolytic enzymes; Microbial biotechnology; Xylanase